Perancangan Kapal Perikanan Dengan Alat Tangkap Gillnet Di Karangsong Indramayu Jawa Barat - Novi Hendri; Erifive Pranatal (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Ships have an important role in fishing operations, because ships are an aspect that determines success in the fishing proses. In order for a gillnet vessel to operate properly, it must have a large length, moderate width, and small draft height because these three values are the main values for ship dimensions. In designing fishing vessels, there are several stages, namely calculating the main dimensions, making lines plan, and calculate the resistance experienced by the ship. This study aims to determine the main dimensions of fishing vessels from gross tonnage in the Karangsong area, as well as to draw a line plan for the main sizes of fishing vessels and determine the resistance of vessels at their service speed. This research was conducted in the Karangsong Indramayu area from March to June 2023. The results of the research on the main sizes of fishing vessels with gillnets are L= 18,1 m, B= 4,6 m, D= 1,8 m, service speed boats designed to range from 0 to 12 knots using the holtrop method, the drag at a speed of 6 knots is 2,5 kN, at a speed of 9 knots is a 16,1 kN, and at a speed of 12 knots it is 49,3 kN.